2020
DOI: 10.1007/s10389-020-01337-5
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the relationship between oral high-risk HPV infection and sexual behavior among over 400 medical professionals in Japan

Abstract: Objectives This study investigated the relationship between oral high-risk HPV (HR HPV) infection and sexual behavior in Japanese medical professionals. Materials and methods We collected oral specimens and a self-administered questionnaire from 234 men and 171 women. Results The oral HR HPV infection prevalence was 4.7% (95% confidence interval [CI]: 3.0-7.2]) overall, 7.3% (95% CI: 4.6-11.3) for men, and 1.2% (95% CI: 0.3-4.2) for women. The number of sex partners had a significant influence on this prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…It may be because fewer participants had more than one sexual partner. However, contrary to the finding in previous studies, which reported that among OHPV positive infections, the number of sexual partners was greater 6,11,18,20,28 …”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…It may be because fewer participants had more than one sexual partner. However, contrary to the finding in previous studies, which reported that among OHPV positive infections, the number of sexual partners was greater 6,11,18,20,28 …”
Section: Discussioncontrasting
confidence: 83%
“…When we stratified according to sexual behavior, we found that oral HR‐HPV positive was more frequently identified in females who have their first sexual debut at an early age, that is, between 14 and 18 years of age. A considerable decrease in the oral HR‐HPV positive was seen with the increasing age from the age at first sexual debut with a nonsignificant association among them, consistent with the studies conducted in Europe and Japan 27,28 . However, studies carried out in the United States and Peru 10,38 reported a significant association between OHPV positive and age at first sexual debut.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations